Analysis of Partial Pilot Filling Phase Noise Compensation for CO-OFDM Systems - Hussin, Saleh; Puntsri, Kidsanapong; Noé, Reinhold (IEEE Photonics Technology Letters)

20-Gb/s PDM-RZ-DPSK Transmission With 40 krad/s Endless Optical Polarization Tracking - Koch, Benjamin; Noé, Reinhold; Sandel, David; Mirvoda, Vitali; Omar, Jan; Puntsri, Kidsanapong (IEEE Photonics Technology Letters)

Lieder singen, Lieder schreiben: ‚Sechs deutsche Lieder‘ op. 14 von Josephine Lang und Reinhold Köstlin - Grotjahn, Rebecca (Liedersingen. Studien zur Aufführungsgeschichte des Liedes)

Höhere Tochter spielen. Musik, Gender, Bürgerlichkeit um 1900 - Grotjahn, Rebecca (Einsichten und Aussichten. Ein interdisziplinärer Auftakt)

‚Mein bessres Ich‘ – Schumanns Myrthen als Selbstbildnis des Künstlers - Grotjahn, Rebecca (Autorschaft – Genie – Geschlecht. Musikalische Schaffensprozesse von der frühen Neuzeit bis zur Gegenwart)

‚Precisely as sung by Her‘ – zur Mediengeschichte des Stars im 19. Jahrhundert - Grotjahn, Rebecca (ShePOP – Frauen. Macht. Musik!)

X-ray Spectroscopic Verification of the Active Species in Iron-Catalyzed Cross-Coupling Reactions - Schoch, Roland; Desens, Willi; Werner, Thomas; Bauer, Matthias (Chemistry - A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Experimental Investigations on the Induced Anisotropy of Mechanical Properties in Polycarbonate Films - Wibbeke, Andrea; Schöeppner, Volker; Mahnken, Rolf (ISRN Materials Science)
The prime aim of this paper is to investigate, with the help of experiments, the induced anisotropy of mechanical properties in polycarbonate films. It is known that a molecular orientation in polymer materials occurs through cold-forming. In this study, cold forming is performed at room temperature on a tensile testing machine. The polycarbonate films are examined in two phases. In the first phase, the specimen is loaded, while the prestrain is varied, and in the second, it is loaded, while the material direction is varied. The main findings are that the prestrain has virtually no influence on the anisotropy and that the material direction does exert a major influence. Furthermore, this paper summarizes comparisons of anisotropic characteristic data, maximum stresses, elasticity moduli and failure strain.

Parameter Identification in Continuum Mechanics: From Hand-Fitting to Stochastic Modelling - Mahnken, Rolf (The History of Theoretical, Material and Computational Mechanics - Mathematics Meets Mechanics and Engineering)

A multi-mechanism model for cutting simulations combining visco-plastic asymmetry and phase transformation - Mahnken, Rolf; Wolff, M.; Cheng, C. (International Journal of Solids and Structures)

Finite Deformation Plasticity with Void Growth and Asymmetric Compression-Tension Behavior - Mahnken, Rolf; Stein, E. (IUTAM Symposium on Computational Mechanics of Solid Materials at Large Strains)

Thermodynamic consistent modeling of polymer curing coupled to visco–elasticity at large strains - Mahnken, Rolf (International Journal of Solids and Structures)

Goal-oriented adaptive refinement for phase field modeling with finite elements - Mahnken, Rolf (International Journal for Numerical Methods in Engineering)

Simulation of strain-induced anisotropy for polymers with weighting functions - Mahnken, Rolf; Dammann, Christian (Archive of Applied Mechanics)

A Multi-Mechanism Model for Cutting Simulations Combining Visco-plastic Asymmetry and Phase Transformation - Cheng, Chun; Mahnken, Rolf; Uhlmann, Eckart; Ivanov, Ivan Mitkov (PAMM)

Eltern- und Familienbildung im Kindergarten. Zwischen gemeinsamer Erziehungsverantwortung, sozialer Teilhabe und frühkindlicher Entwicklungsförderung - Faas, Stefan; Landhäußer, Sandra (Konsens und Kontroversen. Sozialpädagogik und Pädagogik der frühen Kindheit im Dialog)
Thema der vorliegenden Publikation sind aktuelle Entwicklungen und Forschungen an der Schnittstelle zwischen Sozialpädagogik und Kindheitspädagogik. Der Wandel, den das Feld durch u.a. die Folgen des „PISA-Schocks“, die neue Thematisierung von Bildung im Elementarbereich, den U3-Ausbau, familienpolitische Entscheidungen und die Expansion von Studiengängen für Kindheitspädagogik erfährt, wird aus verschiedenen Perspektiven aufgegriffen und wissenschaftlich in zumeist inter- oder transdisziplinärer Weise unter die Lupe genommen. Herausgeberin ist die – seit 2011 unter erweiterter Bezeichnung agierende - „Sektion Sozialpädagogik und Pädagogik der frühen Kindheit“ der Deutschen Gesellschaft für Erziehungswissenschaft. Der Band ist das „Ergebnis eines Dialogs“ (S. 9) von Vertreter/innen der Sozialpädagogik und der Kindheitspädagogik. Er markiert damit einen Wendepunkt im Verhältnis der beiden Bereiche bzw. Teildisziplinen und ihrer entsprechenden Kommissionen innerhalb der DGfE, die Ende der 1990er Jahre unter dem Dach der „Sektion Sozialpädagogik“ vereint wurden und dort eher nebeneinander agierten. Den neuen Orientierungen des vorangegangenen Jahrzehnts Rechnung tragend, veranstalteten die beiden Kommissionen im Sommer 2011 in Erkner bei Berlin eine gemeinsame Tagung, aus der die Beiträge zum vorliegenden Band hervorgegangen sind und im Rahmen derer die Aufnahme der „Pädagogik der frühen Kindheit“ in den Sektionstitel beschlossen wurde. Damit ist der Band auch Ausdruck eines erneuten „Aufeinanderzugehens“, dessen weitere Entwicklung mit Spannung beobachtet werden kann.
Keywords: Erziehungswissenschaft | Soziale Arbeit | Sozialpädagogik | Kindheitsforschung | Kommission

Hydrophobic gold nanoparticles via silane conjugation: chemically and thermally robust nanoparticles as dopants for nematic liquid crystals - Mirzaei, Javad; Urbanski, Martin; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences)
We examine for the first time how chemically and thermally stable gold nanoparticles (NPs), prepared by a silane conjugation approach, affect both the thermal and the electro-optical properties of a nematic liquid crystal (LC), when doped at concentrations ranging from 0.25 to 7.5 wt%. We find that the octadecylsilane-conjugated gold NPs stabilize both the enantiotropic nematic and the monotropic smectic-A phases of the LC host with a maximum stabilization of 2 ° C for the nematic and 3.5 ° C for the smectic-A phases for the mixture containing 1 wt% of the silanized particles. The same mixture shows the lowest values for the Fréedericksz transition threshold voltage and the highest value for the dielectric anisotropy. Generally, all NP-containing mixtures, except mixtures with NP concentrations exceeding 5 wt%, reduce the threshold voltage, increase the dielectric anisotropy and reduce both rise and decay time; the latter particularly at temperatures at least 10 ° C below the isotropic–nematic phase transition on cooling.
Keywords: General Physics and Astronomy; General Engineering; General Mathematics

Microresonator-enhanced electroluminescence of an organic light emitting diode based on a columnar liquid crystal - Vollbrecht, Joachim; Kasdorf, Olga; Quiring, Viktor; Suche, Hubertus; Bock, Harald; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Limit transition between hypergeometric functions of type BC and type A - Rösler, Margit; Koornwinder, Tom; Voit, Michael (Compositio Mathematica)
Abstract Let ${F}_{BC} (λ , k; t)$ be the Heckman–Opdam hypergeometric function of type BC with multiplicities $k= ({k}_{1} , {k}_{2} , {k}_{3} )$ and weighted half-sum $ρ (k)$ of positive roots. We prove that ${F}_{BC} (λ + ρ (k), k; t)$ converges as ${k}_{1} + {k}_{2} → ∞ $ and ${k}_{1} / {k}_{2} → ∞ $ to a function of type A for $t\in { \mathbb{R} }^{n} $ and $λ \in { \mathbb{C} }^{n} $ . This limit is obtained from a corresponding result for Jacobi polynomials of type BC, which is proven for a slightly more general limit behavior of the multiplicities, using an explicit representation of Jacobi polynomials in terms of Jack polynomials. Our limits include limit transitions for the spherical functions of non-compact Grassmann manifolds over one of the fields $ \mathbb{F} = \mathbb{R} , \mathbb{C} , \mathbb{H} $ when the rank is fixed and the dimension tends to infinity. The limit functions turn out to be exactly the spherical functions of the corresponding infinite-dimensional Grassmann manifold in the sense of Olshanski.
Keywords: Algebra and Number Theory

Olshanski spherical functions for infinite dimensional motion groups of fixed rank - Rösler, Margit; Voit, Michael (Journal of Lie Theory 23)

80 Gb/s Decision Feedback Equalizer for Intersymbol Interference - Möller, Lothar; Awny, Ahmed; Junio, Josef; Scheytt, Christoph; Thiede, Andreas (Optical Fiber Communication Conference)
We demonstrate the first 80 Gb/s decision feedback equalizer in various electrical and optical applications. The device, designed in SiGe:C BiCMOS 0.13 μm technology, enables error-free data recovery of heavily distorted signals transmitted at a bandwidth less than 30% of their bit rate. The fastest nonlinear electrical equalizer reported yet utilizes a novel 1-tap look-ahead architecture.

Analysis of Partial Pilot Filling Phase Noise Compensation for CO-OFDM Systems - Hussin, Saleh; Puntsri, Kidsanapong; Noé, Reinhold (IEEE PHOTONICS TECHNOLOGY LETTERS)

Verhör, Bekenntnis, Schweigen – fatale Kommunikationsstrategien in Michael Hanekes Film Das weiße Band - Morrien, Rita (Weimarer Beiträge)

20-Gb/s PDM-RZ-DPSK Transmission With 40 krad/s Endless Optical Polarization Tracking - Koch, Benjamin; Noé, Reinhold; Sandel, David; Mirvoda, Vitali; Omar, Jan; Puntsri, Kidsanapong (IEEE PHOTONICS TECHNOLOGY LETTERS)

An Experiment of Coherent Optical DFT-spread OFDM with Laser Phase Noise - Jan, Omar; Al-Bermani, Ali; Puntsri, Kidsanapong; Sandel, David; Woerdehoff, Christian; Rueckert, Ulrich; Noé, Reinhold (2013 ITG Symposium Proceedings - Photonic Networks)

Die Bedeutung von Kommunikation zwischen Elternhaus und Schule für die Lesekompetenz im Grundschulalter. Vortrag auf der 1. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: "Bildungsverläufe über die Lebensspanne" - Kretschmer, Johanna; Buhl, Heike M.; Hoya, Fabian Karl; Hellmich, Frank

Time-correspondence differential ghost imaging - Li, Ming-Fei; Zhang, Yu-Ran; Luo, Kai Hong; Wu, Ling-An; Fan, Heng (Physical Review A)

A double-threshold technique for fast time-correspondence imaging - Li, Ming-Fei; Zhang, Yu-Ran; Liu, Xue-Feng; Yao, Xu-Ri; Luo, Kai Hong; Fan, Heng; Wu, Ling-An (Applied Physics Letters)

Boundary Behavior of α-Harmonic Functions on the Complement of the Sphere and Hyperplane - Luks, Tomasz (Potential Analysis)

Qualität inklusiven Unterrichts in der Grundschule. Symposium auf der Tagung „Gemeinsam anders lehren und lernen – Wege in die inklusive Bildung“. Gemeinsame Jahrestagung der DGfE Kommission Grundschulforschung und Didaktik der Primarstufe und der DGfE Sektion Sonderpädagogik - Hellmich, Frank; Blumberg, Eva

An Interference Alignment Algorithm for Structured Channels - Lameiro, Christian; Santamaría, Ignacio (Proc. IEEE Work. Signal Process. Advances in Wireless Comm.)
In this paper we propose a new interference alignment (IA) algorithm specifically designed to work with structured channels (e.g., diagonal or block-diagonal). Multiple-input multiple-output (MIMO) structured channels arise when symbol extensions -either in time or frequency- are employed jointly with the spatial dimension in the design of the precoders. In this case, the rank constraint in the direct channels must explicitly be taken into account into the optimization problem to ensure that there is no degrees-of-freedom (DoF) loss. To this end, we propose an algorithm that minimizes the interference leakage while ensuring that the direct links are full rank and the transmitters satisfy a power constraint. The algorithm is based upon an alternating optimization procedure, which solves a generalized eigenvalue problem at each step. We show through simulations the advantages of the proposed algorithm in several scenarios that use symbols extensions or improper (a.k.a. asymmetric) signalling.

Degrees-of-Freedom for the 4-User SISO Interference Channel with Improper Signaling - Lameiro, Christian; Santamaría, Ignacio (Proc.\ IEEE Int.\ Conf.\ Comm.)
It has been recently shown that for the 3-user single-input single-output (SISO) interference channel with constant channel coefficients, a maximum of 1.2 degrees-of-freedom (DoF) are achievable using linear interference alignment schemes when improper (a.k.a. asymmetric) Gaussian signaling is applied. In this paper, we study the 4-user SISO interference channel and provide inner and outer bounds for the total number of DoF achievable for this channel. We prove that at least 4/3 DoF are achievable for the 4-user channel using also linear interference alignment techniques and improper signaling. A simple converse proof shows that no more than 8/5 DoF are achievable for this scheme. Simulation results seem to indicate that the inner bound is in fact tight for this channel, and serve to illustrate the sum-rate improvement with respect to time division multiple access (TDMA) techniques.

Optical Coherence Tomography Assessment of Vessel Wall Degradation in Aneurysmatic Thoracic Aortas - Real, Eusebio; Eguizabal, Alma; Ponton, Alejandro; Val-Bernal, J. Fernando; Mayorga, Marta; Revuelta, Jose; Lopez-Higuera, Jose; Conde, Olga (European Conferences on Biomedical Optics)
OCT images of human aorta from aneurysms reveals elastin disorder and smooth muscle cell alteration when visualizing the intima and media layers of the aortic wall. Results correlate with pathologist diagnosis in aneurysmatic and control aortas.

Quantization-loss reduction for signal parameter estimation - Stein, Manuel; Wendler, Friederike; Mezghani, Amine; Nossek, Josef A. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Linear classifier and textural analysis of optical scattering images for tumor classification during breast cancer extraction - Eguizabal, Alma; Laughney, Ashley M.; Garcia-Allende, P. Beatriz; Krishnaswamy, Venkataramanan; Wells, Wendy A.; Paulsen, Keith D.; Pogue, Brian W.; Lopez-Higuera, Jose; Conde, Olga M. (SPIE Photonics West BIOS, VIII Biomedical Applications of Light Scattering)
Texture analysis of light scattering in tissue is proposed to obtain diagnostic information from breast cancer specimens. Light scattering measurements are minimally invasive, and allow the estimation of tissue morphology to guide the surgeon in resection surgeries. The usability of scatter signatures acquired with a micro-sampling reflectance spectral imaging system was improved utilizing an empirical approximation to the Mie theory to estimate the scattering power on a per-pixel basis. Co-occurrence analysis is then applied to the scattering power images to extract the textural features. A statistical analysis of the features demonstrated the suitability of the autocorrelation for the classification of notmalignant (normal epithelia and stroma, benign epithelia and stroma, inflammation), malignant (DCIS, IDC, ILC) and adipose tissue, since it reveals morphological information of tissue. Non-malignant tissue shows higher autocorrelation values while adipose tissue presents a very low autocorrelation on its scatter texture, being malignant the middle ground. Consequently, a fast linear classifier based on the consideration of just one straightforward feature is enough for providing relevant diagnostic information. A leave-one-out validation of the linear classifier on 29 samples with 48 regions of interest showed classification accuracies of 98.74% on adipose tissue, 82.67% on non-malignant tissue and 72.37% on malignant tissue, in comparison with the biopsy H and E gold standard. This demonstrates that autocorrelation analysis of scatter signatures is a very computationally efficient and automated approach to provide pathological information in real-time to guide surgeon during tissue resection.

Fractal analysis of scatter imaging signatures to distinguish breast pathologies - Eguizabal, Alma; Laughney, Ashley M.; Krishnaswamy, Venkataramanan; Wells, Wendy A.; Paulsen, Keith D.; Pogue, Brian W.; Lopez-Higuera, Jose; Conde, Olga M. (SPIE Photonics West BIOS, VIII Biomedical Applications of Light Scattering)
Fractal analysis combined with a label-free scattering technique is proposed for describing the pathological architecture of tumors. Clinicians and pathologists are conventionally trained to classify abnormal features such as structural irregularities or high indices of mitosis. The potential of fractal analysis lies in the fact of being a morphometric measure of the irregular structures providing a measure of the object’s complexity and self-similarity. As cancer is characterized by disorder and irregularity in tissues, this measure could be related to tumor growth. Fractal analysis has been probed in the understanding of the tumor vasculature network. This work addresses the feasibility of applying fractal analysis to the scattering power map (as a physical modeling) and principal components (as a statistical modeling) provided by a localized reflectance spectroscopic system. Disorder, irregularity and cell size variation in tissue samples is translated into the scattering power and principal components magnitude and its fractal dimension is correlated with the pathologist assessment of the samples. The fractal dimension is computed applying the box-counting technique. Results show that fractal analysis of ex-vivo fresh tissue samples exhibits separated ranges of fractal dimension that could help classifier combining the fractal results with other morphological features. This contrast trend would help in the discrimination of tissues in the intraoperative context and may serve as a useful adjunct to surgeons.

Principal Component Analysis to extract blood oxygenation from theoretical modeling of total diffuse reflectance spectra - Eguizabal, Alma; Garcia-Allende, Pilar; Jentoft, Karin; Symvoulidis, Panagiotis; Lopez-Higuera, Jose; Ntziachristos, Vasilis; Conde, Olga M. (European Conferences on Biomedical Optics)
Endogenous tissue contrast such as decreased hemoglobin saturation aids in cancer localization. Principal component analysis is proposed for blindly oxygenation extraction from total diffuse reflectance spectra obtained by the diffusion approximation.

Input-dependent stability analysis of systems with saturation in feedback - Yu. Pogromsky, Alexander; Matveev, Alexey S.; Chaillet, Antoine; Rüffer, Björn S. (Proc. 52nd IEEE Conf. Decis. Control)
The paper deals with global stability analysis of linear control systems with saturation in feedback driven by an external input. Various new criteria based on non-quadratic Lyapunov functions are proposed, that unlike many previous results, offer better account for the role of the external excitation by providing input-dependent conditions for stability of solutions. For example, it is shown that even if the system fails to satisfy the incremental version of the circle criterion, the stability is guaranteed whenever the uniform root mean square value of the input signal is less than a computable threshold. The general theoretical results are illustrated in the case of the double integrator closed by a saturated linear feedback with an external excitation.

Linear equalization in communications with mismatched modeling using Krylov subspace expansion - Tong, Jun; Schreier, Peter J. (Proc. IEEE Wireless Comm. Networking Conf. (WCNC))

Rezension zu Jean Baudrillard: Similucares et Simulation 1981/Simulacra and Simulation 1994 - Alpsancar, Suzana (Nachdenken über Technik)

Rezension zu Vilém Flusser: Kommunikologie 1996; Vom Subjekt zum Projekt 1994 - Alpsancar, Suzana (Nachdenken über Technik)

Gummilinsen. Wolfgang Königs Vision von Technikgeschichtsschreibung - Alpsancar, Suzana; Kettner, Matthias (Erwägen-Wissen-Ethik (EWE))

On the selective aerobic oxidation of benzyl alcohol with Pd/Au-nanoparticles in batch and flow - Alex, Hannes; Steinfeldt, Norbert; Jähnisch, Klaus; Bauer, Matthias; Hübner, Sandra (Nanotechnology Reviews)
Abstract Nanoparticles (NP) have specific catalytic properties, which are influenced by parameters like their size, shape, or composition. Bimetallic NPs, composed of two metal elements can show an improved catalytic activity compared to the monometallic NPs. We, herein, report on the selective aerobic oxidation of benzyl alcohol catalyzed by unsupported Pd/Au and Pd NPs at atmospheric pressure. NPs of varying compositions were synthesized and characterized by UV/Vis spectroscopy, transmission electron microscopy (TEM), and small-angle X-ray scattering (SAXS). The NPs were tested in the model reaction regarding their catalytic activity, stability, and recyclability in batch and continuous procedure. Additionally, in situ extended X-ray absorption fine structure (EXAFS) measurements were performed in order to get insight in the process during NP catalysis.
Keywords: Surfaces; Coatings and Films; Process Chemistry and Technology; Energy Engineering and Power Technology; Biomaterials; Medicine (miscellaneous); Biotechnology

Direct Observation of Molecular Orbital Mixing in a Solvated Organometallic Complex - Suljoti, Edlira; Garcia-Diez, Raul; Bokarev, Sergey I.; Lange, Kathrin M.; Schoch, Roland; Dierker, Brian; Dantz, Marcus; Yamamoto, Kenji; Engel, Nicholas; Atak, Kaan; Kühn, Oliver; Bauer, Matthias; et al. (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Trinuclear Diamagnetic Nickel(II) Complexes with Bridging 3‐Arylpyrazolato Ligands - Salih, Kifah S. M.; Bergner, Susann; Kelm, Harald; Sun, Yu; Grün, Anneken; Schmitt, Yvonne; Schoch, Roland; Busch, Mark; Deibel, Naina; Bräse, Stefan; Sarkar, Biprajit; Bauer, Matthias; et al. (European Journal of Inorganic Chemistry)
Keywords: Inorganic Chemistry

The chemical sensitivity of X-ray spectroscopy: high energy resolution XANES versus X-ray emission spectroscopy of substituted ferrocenes - Atkins, Andrew J.; Bauer, Matthias; Jacob, Christoph R. (Physical Chemistry Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Valence-to-Core X-Ray Emission Spectroscopy of Iron-Carbonyl Complexes: Implications for the Examination of Catalytic Intermediates - Delgado-Jaime, Mario Ulises; DeBeer, Serena; Bauer, Matthias (Chemistry - A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

X-ray Spectroscopic Verification of the Active Species in Iron-Catalyzed Cross-Coupling Reactions - Schoch, Roland; Desens, Willi; Werner, Thomas; Bauer, Matthias (Chemistry - A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Hierarchically structured copper gallium spinels through microwave hydrothermal methods - Conrad, Franziska; Bauer, Matthias; Weyeneth, Stephen; Zhou, Ying; Hametner, Kathrin; Günther, Detlef; Patzke, Greta Ricarda (Solid State Sciences)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Relativität - Alpsancar, Suzana (Lexikon der Raumphilosophie)